Odpowiedzi

2010-02-23T20:57:22+01:00
A) 6xy-5xy+4xy-3xy+2xy-xy=3xy


b) 2,5a-a-4a+6,5a-3,5a=0.5a

c) 0,3x-0,4x+0,5x-0,6x+0,7x=0.5x

e) 1/2a(do kwadratu)+1/3a(do kwadratu)+1/6a(do kwadratu)-2a(do kwadratu)=3+2+1-12/6=-6/6=-1a do kwadratu
12 3 12
2010-02-23T20:58:22+01:00
A) 6xy-5xy+4xy-3xy+2xy-xy=3xy
b) 2,5a-a-4a+6,5a-3,5a=-0,5a
c) 0,3x-0,4x+0,5x-0,6x+0,7x=0,5x
d) 696y-969y+69y-96y=-300y
e) 1/2a(do kwadratu)+1/3a(do kwadratu)+1/6a(do kwadratu)-2a(do kwadratu)=-3 i 29/36a2
20 4 20
2010-02-23T21:04:44+01:00
6xy-5xy+4xy-3xy+2xy-xy=3xy
2,5a-a-4a+6,5a-3,3a=-1,2a
0,3x-0,4x+0,5x-0,6x+0,7x=0,5x
696y-969y+69y-96y=-300y
tak jak wyżej =-a do kwadratu

pomyliłam się w przepisywaniu b)2,5a-a-4a+6,5a-3,5a=0,5a
9 4 9